Electricity carbon intensity in European Member States: Impacts on GHG emissions of electric vehicles. (October 2018) - Moro, Alberto; Lonza, Laura
Graphical abstract: Well-to-Wheels emissions of electric vehicles in the Member States of the European Union. Highlights: GHG intensities of electricity consumed in the EU Member States have been calculated for 2013. The import of electricity is a critical factor affecting the carbon intensity of a Country. CI of electricity consumed at low voltage results, in average, 447 gCO2 eq/kWh. Using EVs, in EU, saves on average 50–60% of GHG emissions compared to internal combustion engines. Abstract: The Well-To-Wheels (WTW) methodology is widely used for policy making in the transportation sector. In this paper updated WTW calculations are provided, relying on 2013 statistic data, for the carbon intensity (CI) of the European electricity mix; detail is provided for electricity consumed in each EU Member State (MS). An interesting aspect presented is the calculation of the GHG content of electricity traded between Countries, affecting the carbon intensity of the electricity consumed at national level. The amount and CI of imported electricity is a key aspect: a Country importing electricity from another Country with a lower CI of electricity will lower, after the trade, its electricity CI, while importing electricity from a Country with a higher CI will raise the CI of the importing Country. In average, the CI of electricity used in EU at low voltage in 2013 was 447 gCO2 eq/kWh, which is the 17% less compared to 2009. Then, some examples of calculation of GHG emissions from the use of electric vehicles (EVs) compared to internal combustion engine vehicles are provided. The use of EVs instead of gasoline vehicles can save (about 60% of) GHG in all or in most of the EU MSs, depending on the estimated consumption of EVs. Compared with diesel, EVs show average GHG savings of around 50% and not savings at all in some EU MS.